Nitric oxide modulates ionic transport in the isolated intestine of the eel, anguilla anguilla - TRISCHITTA, F.; FAGGIO, C.; Pidala, P. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2007)
We investigated the role of NO (nitric oxide) in the isolated intestine of the sea water adapted eel, by testing the effect of various donors on I(sc) (short-circuit current), due to net Cl(-) absorption in the control conditions. We found that the endogenous NO-synthase substrate l-arginine as well as two different NO donors, SNP (sodium nitroprusside) and SIN-1 (3-morpholinosydnonimine), produced a slow and gradual decrease of I(sc). The effect of SNP was reduced by the pretreatment with ODQ (1H-[1,2,4]oxadiazolo-[4,3-a]quinoxalin-1-one), a specific inhibitor of the soluble guanylyl cyclase, suggesting the involvement of cGMP (cyclic GMP) in some physiological actions of NO. The effect of the NO donors on I(sc) was similar to that observed when the tissues were perfused with solution in which the HCO(3)(-) buffer was substituted with Hepes buffer. In addition the NO donors produced a negligible effect on I(sc) when the tissues were perfused with Hepes buffer or in the presence of bilateral SITS(4-Acetoamido-4'-iso-thiocyanatostilbene-2,2'disulphonic acid), an inhibitor of the HCO(3)(-) transport mechanisms, operating on both cell membranes of the eel enterocyte and responsible for HCO(3)(-) uptake by the cell. Based on these observations we suggest that NO regulates I(sc) and hence the transepithelial ion transport indirectly by modulating the endocellular concentration of HCO(3)(-) and/or H(+). In addition it is likely that NO modulates the permeability of the paracellular pathway since SNP produced also an increase of the tissue conductance and a decrease of the magnitude of the dilution potential.